The Influence of 3-Dimensional Image Media to Improve Learning Outcomes of Social Studies Concepts With The Beauty of Togetherness Traditional Clothing Theme in - Ayatulloh Masduki, Reza; Nuruddin, Muhammad (IJPSE : Indonesian Journal of Primary Science Education, 2021)
This study aims to determine the influence of 3-dimensional image media to improve learning outcomes of social studies concepts with beauty of togetherness traditional clothing theme in grade four at SDN Kaliwungu II, Jombang. This study uses a quantitative approach. - Posttest. The population in this study were all students of grade 4 at SDN Kaliwungu II, totaling 21 students. The problem in education is that the learning that is carried out is less attractive, meanwhile the educators are required to be creative in improving the quality of education such as using media in learning. The results of the study can be seen from the t test (paired t test) obtained t_count (6,3814) > t_table (2,0859.). The results of the research on the application of image media obtained 82%, which is very good. From these results, it can be stated that there is an effect of using 3- dimensional image media to improve learning outcomes of social studies concepts with beauty of togetherness traditional clothing theme in grade four at SDN Kaliwungu II, Jombang